Diagonal compression cyclic testing of unreinforced and reinforced masonry walls. (11th January 2023) - Biolzi, Luigi; Cattaneo, Sara; Crespi, Pietro; Scamardo, Manuela; Vafa, Navid
Highlights: Diagonal compression tests were conducted on steel reinforced plaster masonry walls. The investigated parameters were the wall thickness and the plaster thickness. UPV measurements were used to detect masonry heterogeneity and plaster detachments. A significant improvement of strength and ductility of retrofitted walls was observed. Abstract: Steel reinforced plasters (SRP) are a traditional strengthening solution of existing masonry structures. SRPs consist of a thin layer of cementitious mortar or concrete (jacket) that incorporates a steel reinforcing mesh tied to a series of steel bent connectors embedded in the underlying masonry. Despite the recent development of more innovative retrofitting methods, SRPs are still widely adopted because of their low costs and effectiveness in terms of improved performance. In the present paper, a comprehensive experimental program on brickwork masonry walls is presented. The results are intended as a contribution to the knowledge of in-plane behavior of masonry strengthened with SRPs. Unreinforced and plastered masonry walls were subjected to cyclic diagonal compression loading under displacement control. Different thicknesses of walls (2 and 3 wythes) and plasters (30 and 50 mm) were selected. The performances of the plastered and non-plastered specimens were analyzed and compared. The results showed that the SRPs increased considerably the performance of the walls in terms of both strength and deformation capacity. The plaster's thickness had limited effects on the load carrying capacity of the walls, whereas it had a significant effect on their ductility. Finally, the connectors used to tie the steel mesh to the masonry walls played an essential role and avoided large out-of-plane displacements of the plaster layer after its detachment, thus preventing instability phenomena.